Intizar Hussain’s ‘‘Aakri Aadmi’’: Critical Study - Ali, Muhammad Said; Khurshid, Abid; Zahra, Shazma (sourcecoder, 2022)
Intizar Hussain is a well-known Urdu fiction writer. He made a name for himself in novel, short story writing, drama, travelogue, criticism, journalism, column writing, sketch writing and translation. He wrote 4 novels and 9 story books. He has chosen the local atmosphere of the suncontinent for the story writing instead of the West. "Aakhri Aadmi" is Intezar Hussain’s third legendary collection. There are eleven stories in it. In which the colour of symbols, myths and ancient stories is prominent. This article is a critical study of the stories of this mythical collection.